PERANAN MEDIA CETAK DALAM PEMBERIAN INFORMASI LINGKUNGAN HIDUP DI DAERAH ISTIMEWA YOGYAKARTA - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
The regulation on environmental information is new, which is stated in Act Number 23 of 1997 regarding Environmental Management. The print media as one of the environmental constituents must share the responsibility in distributing the information, at least for assisting the community which usually is a potential victim of environmental pollution. The aim of this research is to find out how the print media implements its function as a provider of environmental information and to understand the obstacles in providing that information. The research was done within the Special Province of Yogyakarta. The data were collected by carrying out interview and giving questionnaire (combination of closed and open system) to Kedaulatan Rakyat and Kompas readers. The samples were determined by using the purposive sampling method. The data were analyzed qualitatively. The research shows that in implementing its function as a social control institute, the print media files the report which contain the environmental substance, whereas as a social education institute the print media provides critical comment and information to the community. The obstacles in providing environmental information can be divided into